2011
DOI: 10.1002/jbm.a.33105
|View full text |Cite
|
Sign up to set email alerts
|

Molecular plasma deposited peptides on anodized nanotubular titanium: An osteoblast density study

Abstract: A large amount of work is currently being conducted to design, fabricate, and characterize materials coated or immobilized with bioactive molecules for tissue engineering applications. Here, a novel method, molecular plasma deposition (MPD), is introduced with can efficiently coat materials with numerous bioactive peptides. Specifically, here, RGDS (arginine-glycine-aspartic acid-serine), KRSR (lysine-arginine-serine-arginine), and IKVAV (isoleucine-lysine-valine-alanine-valine) were coated on anodized nanotub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Electrochemical anodization is a process that produces a durable and corrosion-resistant anodic oxide layer on a metal surface that protects the inner bulk metal [ 14 ]. Nanotube coatings by anodization have received increased attention recently, for the manufacturing of orthopedic and dental implants [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Numerous researchers have found that the coating morphology has a great impact on the biocompatibility of metallic implants [ 15 , [42] , [43] , [44] ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical anodization is a process that produces a durable and corrosion-resistant anodic oxide layer on a metal surface that protects the inner bulk metal [ 14 ]. Nanotube coatings by anodization have received increased attention recently, for the manufacturing of orthopedic and dental implants [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Numerous researchers have found that the coating morphology has a great impact on the biocompatibility of metallic implants [ 15 , [42] , [43] , [44] ].…”
Section: Introductionmentioning
confidence: 99%
“…KRSR increased osteoblast adhesion and osteogenic gene expression [ 171 , 172 , 177 , 178 ]. Anodized nanotubular titanium coated with KRSR, RGDS (arginine-glycine-aspartic acid-serine) and molecular plasma deposition increased osteoblast density compared with uncoated substrates [ 174 ]. Likewise, KRSR and RGD coated on titanium promoted the greatest osteoblast densities relative to untreated titanium [ 175 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the peptide-modified material is removed from the chamber, followed by washed and dried. For example, Balasundaram et al [ 120 ] deposited arginine-glycine-aspartic acid-serine (RGDS), lysine-arginine-serine-arginine (KRSR), and isoleucinelysine-valine-alanine-valine (IKVAV) peptides on the surface of anodized titanium substrate respectively by this method. A high voltage of 20 kV was applied between the substrate and the needle.…”
Section: The Commonly-used Methods To Prepare Peptide-modified Bone Rmentioning
confidence: 99%